Adherence to neonatal hypoglycaemia guidelines: A retrospective cohort study. (22nd June 2019) - Alsweiler, Jane M; Gomes, Leanora; Nagy, Tess; Gilchrist, Catherine A; Hegarty, Joanne E
Abstract : Aim: To determine if the routine use of automatically calculated birthweight centiles prior to discharge from the delivery unit is associated with improved adherence to the neonatal hypoglycaemia guideline. Methods: We conducted retrospective audits of adherence to the neonatal hypoglycaemia guideline in a tertiary maternity hospital in Auckland, New Zealand in a randomly selected cohort of newborn infants at risk of neonatal hypoglycaemia before (2011) and after (2015) the introduction of routine use of calculated birthweight centiles for all infants. The primary outcome was adherence to the guideline, defined as (i) blood glucose concentration screening in the first 48 h after birth; (ii) the initial measurement taken 1–2 h after birth; and (iii) at least three consecutive blood glucose concentrations ≥2.6 mmol/L, over 12 h, prior to cessation of screening. Results: The audits examined the records of 400 infants (200 each in 2011 and 2015) to determine guideline adherence. Adherence improved from 2011 to 2015 (59/200 (30%) vs. 95/200 (48%), P < 0.001), with the largest improvement in large‐for‐gestational age infants (7/50 (14%) vs. 25/50 (50%), P = <0.001). Screened infants whose care was adherent to the guideline had a higher incidence of hypoglycaemia detection (adherent, 64/154 (42%) vs. non‐adherent, 34/246 (14%), P < 0.001). Conclusions: The routine use of calculated birthweight centiles was associated with improved adherence to the neonatal hypoglycaemia guideline and increased detection of neonatal hypoglycaemia in at‐risk infants. Thus, identifying practices that improve guideline adherence may improve the detection of hypoglycaemia in asymptomatic at‐risk infants.